The Implementation Of Cooperative Learning Model Type Jigsaw To Improve The Understanding Of Biological Concept Of Students In Class XI IPA 3 SMA Negeri 5 Kendari - La Haya (Journal of Biological Science and Education, 2019)
This study aims to improve the understanding of biology concepts of students of class XI IPA 3 in SMA Negeri 5 Kendari by applying Jigsaw type cooperative learning models. This research was conducted in the second semester of the academic year 2013/2014. This type of research was a classroom action research (PTK) Kemmis and Taggart with three learning cycles. Each cycle goes through four stages: (1) planning; (2) implementing actions; (3) observation and (4) reflection. The data source of this research was the measurement of students’ worksheets as a test of understanding concepts in cycle I, cycle II and cycle III. The data obtained were analyzed using descriptive analysis. From the results of the study, it was found that students' understanding of biology concepts in the first cycle with a mean of 77.68%; the second cycle was 87.20% and the third cycle was 91.37%. It can be concluded that the implementation of the Jigsaw cooperative learning model can improve the understanding of the biology concepts of students of class XI IPA 3 at SMA Negeri 5 Kendari.  Keywords:  Jigsaw, Conceptual Understanding